PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN DIMEDIASI OLEH KOMITMEN ORGANISASI PADA PEGAWAI SEKRETARIAT DPRD KABUPATEN BENGKALIS - Sri Rahayu Lestari; Susi Hendriani; David Chairilsyah (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2019)
The research held in Bengkalis Regency Secretariate of House of Representative. The aim is to know the direct and indirect effect of leadership and organizational culture toward employee’s performance that mediated by organizational commitment. Population are all member of Bengkalis Regency Secretariate of House of Representative. Census method was employed to determine the 84 employees as the sample. Data analysis tool is descriptive quantitative by using path analysis. The study reveals that leadership have no significant effect toward employee’s performance, but when mediated by organizational commitment the employee’s performance can be enhanced significantly by the leadership. Meanwhile, organizational culture has a direct and very significant impact toward employee’s performance. Indirectly, organizational commitment mediates the effect of organizational culture towards employee’s performance.